2018
DOI: 10.1589/jpts.30.481
|View full text |Cite
|
Sign up to set email alerts
|

Effects of McGill stabilization exercises and conventional physiotherapy on pain, functional disability and active back range of motion in patients with chronic non-specific low back pain

Abstract: [Purpose] The aim of this study was to compare the effects of “McGill stabilization exercises” and “conventional physiotherapy” on pain, functional disability and active back flexion and extension range of motion in patients with chronic non-specific low back pain. [Subjects and Methods] Thirty four patients with chronic non-specific low back pain were randomly assigned to McGill stabilization exercises group (n=17) and conventional physiotherapy group (n=17). In both groups, patients performed the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…All included studies adopted a randomised controlled design (RCT). The main inclusion criterion was (chronic) non-specific low back pain ≥ 4 weeks 22 , ≥ 6 weeks 23 , ≥ 7 weeks 24 , ≥ 8 weeks [25][26][27] , ≥ 12 weeks , ≥ 24 weeks [56][57][58] and ≥ 2 year history 59 , whilst in 11 [60][61][62][63][64][65][66][67][68][69][70] studies this information was not presented. The baseline pain, effect sizes (Cohen's d, stabilisation exercise group only) for pain and disability are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All included studies adopted a randomised controlled design (RCT). The main inclusion criterion was (chronic) non-specific low back pain ≥ 4 weeks 22 , ≥ 6 weeks 23 , ≥ 7 weeks 24 , ≥ 8 weeks [25][26][27] , ≥ 12 weeks , ≥ 24 weeks [56][57][58] and ≥ 2 year history 59 , whilst in 11 [60][61][62][63][64][65][66][67][68][69][70] studies this information was not presented. The baseline pain, effect sizes (Cohen's d, stabilisation exercise group only) for pain and disability are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…1 Ctrl. 2 LBP ≥ 12 weeks 240, 80, 80, 80 51.9 ± 15.3, 54.8 ± 15.3, 54.0 ± 14.4 165/75 VAS (0–10), 6.3 ± 2.0, 6.5 ± 2.1, 6.2 ± 2.0 4: 0; 8, 24; 48 VAS (0–10) 0.92 RMDQ SE: 1.15 Franca, 2012 36 RCT, 2 SE Ctrl LBP ≥ 12 weeks 30, 15, 15 42.1 ± 8.2, 41.5 ± 4.4 N.A VAS (0–10), 5.94 ± 1.56, 6.35 ± 1.51 2: 0; 6 VAS (0–10) SE: 3.77 ODI SE: 3.83 Ghorbanpour, 2018 57 RCT, 2 SE Ctrl LBP ≥ 24 weeks 30, 15, 15 23.8 ± 3.5, 20.9 ± 1.2 16/14 VAS (0–10), 29.5 ± 4.8, 28.3 ± 6.5 2: 0; 6 VAS (0–100) SE: 0.94 Persian version of the Quebec Low Back Pain Disability Scale Questionnaire SE: 0.33 Hosseinifar, 2013 37 RCT, 2 SE Ctrl LBP ≥ 12 weeks 30, 15, 15 40.1 ± 10.8, 36.6 ± 8.2 N.A VAS (0–100), 4.33 ± 1.58, 4.40 ± 1.95 2: 0; 6 VAS (0–100) d = 1.77 FRI questionnaire d = 1.45 Hwang, 2013 71 RCT, 3 SE Ctrl. 1 Ctrl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Base on a review, Cuenca-Martínez et al [5] found that classical physiotherapy procedures were ineffective in the treatment of chronic nonspeci c low back pain. Ghorbanpour et al [23] reported that conventional physiotherapy was not as effective as exercise in reducing pain and improving function in patients with low back pain. The study showed that dry needling provided more therapeutic bene ts compared with classical physiotherapy for patients with low back pain [24] , although there was no follow-up period to evaluate the long-term effects.…”
Section: Discussionmentioning
confidence: 99%